Effect of a 5‐HT 2c receptor agonist on urethral closure mechanism in healthy women - Klarskov, Niels; Van Till, Oliver; Sawyer, Will; Cernus, Dirk (Neurourology and urodynamics, 2019)
To evaluate the effect of ASP2205, a selective serotonin 5-HT receptor agonist, and Duloxetine on the urethral pressure in healthy female subjects. Healthy females aged 18 to 55 years were recruited for this phase 1, single site, placebo-controlled, randomized, four-period, cross-over study. The interventions were single oral doses of 10 and 60 mg ASP2205, 80 mg duloxetine, and placebo. As a pharmacodynamics endpoint, opening urethral pressure (OUP), corrected for placebo, was measured using urethral pressure reflectometry under both resting and squeezing condition of the pelvic floor at predose and 3, 6, 12, and 24 hours after dosing. Safety and tolerability of ASP2205 were also compared with duloxetine and placebo. Eighteen healthy women signed informed consent, however, one dropped out before dosing and one dropped out after the first period, therefore, 16 subjects completed the study. Duloxetine significantly increased the OUP during both resting and squeezing condition (maximal increase 18.1 and 16.8 cmH O, respectively). Both doses of ASP2205 did not increase OUP at any time point. During squeezing OUP decreased significantly in the ASP2205 60 mg group from 6 to 24 hours after dosing. All subjects experienced predominantly central nervous system-related side effects (eg, dizziness and nausea) during ASP2205 treatment, which was most pronounced at 60 mg. ASP2205, a serotonin 5-HT receptor agonist, does not increase the urethral pressure and it is therefore unlikely that 5-HT receptor agonists can be used as a treatment for stress urinary incontinence. ASP2205 was less well tolerated than the high dose of duloxetine.